Textbook of nanoscience and nanotechnology - Murty, B. S.; Ohio Library and Information Network (Berlin ; London : Springer, 2013)
This book covers the broad sweep of nanoscience and technology: terminology, historical perspectives of this scientific domain, unique and widely differing properties, advances in the various synthesis, consolidation and characterization techniques and more.
The Big World of Nanomaterials.- Unique properties of nanomaterials.- Synthesis Routes.- Application of Nanomaterials.- Tools to Characterise Nanomaterials.- Nanostructured materials of high application potential.- Concerns and challenges in nanotechnology.
Keywords: Nanotechnology; Nanoscience